Tradições que se refazem - Ria Lemaire (Estudos de Literatura Brasileira Contemporânea)
This article discusses the relationship between two traditions the tradition of the leaflet of cordel narratives, coming from orality, made and re- made in handwriting and in writing, and the tradition of the scientific discourse about the leaflet, built by means of the intellectual discourse that intertwine in a game of authority and legitimacy over what is tradition in the context of production, reception and criticism on the cordel.